Clinical characteristics of status epilepticus in children in a third level hospital of Lima - Segovia-Sanchez, Frank A. (2022)
Status Epilepticus (SE) in children exhibits high levels of morbidity and mortality and has been poorly studied in Perú. Objective: To describe the frequency and clinical characteristics of children with Status Epilepticus treated at Cayetano Heredia Hospital in Lima. Material and Methods: Retrospective and observational study, case series type, in children under 14 years of age, with Status Epilepticus treated between January and December of 2021. Results: SE was recorded in 28.8% of children with epileptic seizures seen during 2021. Twenty-three children presenting 46 SEs were included. The median age was 2 years, the majority (73,9%) being males, with diagnosis of epilepsy or brain malformation (21.7%) and treated in the pediatric emergency (91%). The predominant semiological pattern was of generalized motor type (52.2%), with remote symptomatic etiology (73.9%), and EEG recorded in a 63% of all cases, mainly reported as normal (75,9%). The median duration was 22 minutes of total resolution, 7 minutes, and of partial resolution, 2 minutes. Midazolam was used as the first line of treatment (78%), and phenytoin as the second line (85%). Conclusions: SE was a frequent condition observed in children throughout the year 2021. Most affected children were male, the predominant etiology was remote symptomatic, and the most common semiological type was the generalized motor. The children were treated according to international management guidelines. A systematic epidemiological surveillance approach is highly encouraged.